Radiographic evaluation of alveolar ridge augmentation with non resorbable hydroxyapatite alloplastic grafts: nine months follow up - Gil-Cárdenas, Félix Antonio (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: the purpose of this study was to determine radiographically the percentage of stability of alveolar ridge height in the maxilla and the mandible in patients subjected to pre prosthetic surgery of ridge augmentation with non resorbable HA implants. Methods: the study was performed in 15 patients in whom reproducible measurements were taken. For the maxilla: (A) From Anterior Nasal Spine; (B right and left) from the lowest border of the nasal fossae; (C right and left) from the lowest border of the orbit. For the mandible: (E) from the lowest border of the mandible passing through symphysis; (F right and left) passing through the mental foramen; (G right and left) passing 5 mm posterior to the mental foramen; (H right and left) passing 10 mm posterior to mental foramen. All measurements were performed before surgery, immediately after and, nine months after surgery. Results: the different points of the maxilla were averaged (PPMXS) and a height loss between 6.29% and 33.6% was observed, with an average of 17.36%. For the mandible (PPMXL) variations ranging from 6.31% of augmentation to 18.8% loss were observed, with an average of 2.54%. Conclusions: HA implants allow reestablishment of adequate alveolar ridge height. The alveolar ridge height initially obtained presents a decrease percentage in height for the maxilla of 17.36% and 2.54% for the mandible after nine months follow up.